2021
DOI: 10.3390/ijms22157873
|View full text |Cite
|
Sign up to set email alerts
|

DNA Dynamics under Periodic Force Effects

Abstract: The sensitivity of DNA to electromagnetic radiation in different ranges differs depending on various factors. The aim of this study was to examine the molecular dynamics of DNA under the influence of external periodic influences with different frequencies. In the present paper, within the framework of a mechanical model without simplifications, we investigated the effect of various frequencies of external periodic action in the range from 1011 s−1 to 108 s−1 on the dynamics of a DNA molecule. It was shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Absorption of microwave radiation by DNA has been observed to induce changes in living organisms [42,43], but the exact mechanism by which microwaves interfere with DNA function is unknown. Exposure of DNA and protein molecules to microwave radiation does not change their structure, but can, under certain conditions, affect their chemical bonds [44]. Experiments conducted by Shamis et al [45] have demonstrated that exposing E. coli cells to microwave radiation under sublethal temperature conditions causes the cell membrane to undergo a reversible, electrokinetic induction without any bactericidal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of microwave radiation by DNA has been observed to induce changes in living organisms [42,43], but the exact mechanism by which microwaves interfere with DNA function is unknown. Exposure of DNA and protein molecules to microwave radiation does not change their structure, but can, under certain conditions, affect their chemical bonds [44]. Experiments conducted by Shamis et al [45] have demonstrated that exposing E. coli cells to microwave radiation under sublethal temperature conditions causes the cell membrane to undergo a reversible, electrokinetic induction without any bactericidal effects.…”
Section: Discussionmentioning
confidence: 99%
“…В качестве перспективных лабораторных маркеров наркопатологии рассматривают различные молекулы, образующиеся в организме больных в ответ на введение наркотической субстанции. Такими молекулами могут быть некоторые специфические белки нервной ткани, субстраты эндотоксикоза, нейромедиаторы и ферменты их обмена, рецепторы нейромедиаторов и антитела к ним, про-и противовоспалительные факторы, такие как цитокины, компоненты антиоксидантной системы и маркеры окислительного стресса [3][4][5][6]. Наиболее интересными ввиду более высокой специфичности являются белковые маркеры.…”
Section: Introductionunclassified
“…For this reason, mathematical modeling is one of the main modern methods for studying DNA molecular dynamics, its mechanical movements, open states, denaturation bubbles [ 5 , 6 , 7 ]. This method, despite several simplifications, allows us to consider various aspects of DNA functioning with great accuracy [ 8 , 9 , 10 ]. In the article [ 11 ], using a combination of atomic force microscopy (AFM) and modeling of atomic molecular dynamics (MD), an attempt was made to experimentally observe the dynamics of open states.…”
Section: Introductionmentioning
confidence: 99%